Angelwings : contemporary queer fiction from Taiwan - Martin, Fran, 1971- (University of Hawai'i Press, 2003)
Lesbian and gay--or queer--fiction (known in Mandarin as tongzhi wenxue) constitutes a major contribution to Taiwanese literature, as evidenced by the remarkable number of prestigious literary awards won by many of the authors of the short stories presented here. Indeed, the meteoric rise of this new genre was a defining feature of Taiwan's literary scene in the 1990s. Queer fiction was also instrumental in forming self-identifying subcultural gay readerships, thus serving a significant political function. But most strikingly, this fiction has been immensely popular with general readers in Taiwan, Hong Kong, and Singapore, as well as in diasporic Chinese communities worldwide. The startlingly fresh, brave voices that speak through these stories attest to the powerful social ferment of the past ten years in Taiwan, which have witnessed a revolution in discourses on sex and sexuality in the public sphere. Contributors: Chu T'ien-Wen, Qiu Miaojin, Chu T'ien-Hsin, Hsu Yoshen, Lin Yuyi, Lin Chun Ying, Chen Xue, Hong Ling, Chi Tawei, Wu Jiwen.